What Factors Influence Patient Measures of Safety Among Adults? - Kim Y; Nam E (Risk Management and Healthcare Policy)
Yujeong Kim,1 Eunhee Nam1,2 1College of Nursing, Research Institute of Nursing Innovation, Kyungpook National University, Daegu, Republic of Korea; 2Health Insurance Review and Assessment Service, Wonju, South KoreaCorrespondence: Eunhee Nam, Health Insurance Review and Assessment Service, Review and Assessment Research Department, 60, Hyeoksin-ro, Wonju-si, Gangwon State, Republic of Korea, 26465, Tel +082-33-739-0941, Fax +082-33-811-7433, Email dmsgml7278@naver.comPurpose: This study aimed to examine the level of patient measures of safety and identify the influencing factors of patient measures of safety among Korean.Methods: This study was a cross-sectional study. From February 7 to February 12, 2024, data were collected through a structured on-line questionnaire consisting of items about general characteristics, patient safety knowledge, nurse–patient interaction, experience of patient participation, willingness to participate in patient safety, and patient measures of safety involving 330 adults. Since there were no incomplete responses, data from all 330 participants were included in the final analysis. The collected data were analyzed using descriptive statistics, t-test, chi-square test, analysis of variance, post-hoc test, correlational analysis, and regression analysis.Results: Patient measures of safety showed significant positive correlations with patients’ safety knowledge, nurse–patient interaction, patient experience in participating in safety activities, and patients’ willingness to participate in safety activities. The employment status, nurse–patient interaction, patient experience in safety activities, and willingness to participate in safety activities were identified as significant factors affecting patient measures of safety.Conclusion: Enhancing nurse–patient interaction—a crucial determinant of patient safety measures—would require implementing effective communication programs. Additionally, it is significant to facilitate patient expression of safety concerns and establish a patient-centered safety monitoring and feedback system. This would actively promote patient participation in safety activities.Keywords: patient safety, nurse-patient relations, patient participation, patient reported outcome measures